-2(3x-2)+18x=2(3x+16)-4

Simple and best practice solution for -2(3x-2)+18x=2(3x+16)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x-2)+18x=2(3x+16)-4 equation:


Simplifying
-2(3x + -2) + 18x = 2(3x + 16) + -4

Reorder the terms:
-2(-2 + 3x) + 18x = 2(3x + 16) + -4
(-2 * -2 + 3x * -2) + 18x = 2(3x + 16) + -4
(4 + -6x) + 18x = 2(3x + 16) + -4

Combine like terms: -6x + 18x = 12x
4 + 12x = 2(3x + 16) + -4

Reorder the terms:
4 + 12x = 2(16 + 3x) + -4
4 + 12x = (16 * 2 + 3x * 2) + -4
4 + 12x = (32 + 6x) + -4

Reorder the terms:
4 + 12x = 32 + -4 + 6x

Combine like terms: 32 + -4 = 28
4 + 12x = 28 + 6x

Solving
4 + 12x = 28 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
4 + 12x + -6x = 28 + 6x + -6x

Combine like terms: 12x + -6x = 6x
4 + 6x = 28 + 6x + -6x

Combine like terms: 6x + -6x = 0
4 + 6x = 28 + 0
4 + 6x = 28

Add '-4' to each side of the equation.
4 + -4 + 6x = 28 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = 28 + -4
6x = 28 + -4

Combine like terms: 28 + -4 = 24
6x = 24

Divide each side by '6'.
x = 4

Simplifying
x = 4

See similar equations:

| 3x^2+15x-40=0 | | 5x-20=3(4-4) | | 8/9*x=-48 | | 4[3-(2-4x)]+2x=2(9x+3)-2 | | 27a^3+18a^2+3a=0 | | 2.5+x=4 | | 5/4-2i= | | 6x+(-20)=20 | | 4-3(3x+3)=5-4x | | 6-20=20 | | 6+(-20)=20 | | 50x^2-98x=0 | | (3z-u)(5z+5u)= | | 28/44 | | 502(x+3)+3.7(2-x)=3 | | 1/8*1/3=x | | (c^2+c-1)(c^2+7c-9)= | | 2x-3=-2x-7 | | 1/3+1/2=x | | 2h+9=61 | | (2-8i)(4+I)= | | f(x)=6x/5x-25 | | 6+(-20)=0 | | 6.15x+4=37.8225+2x | | 2r+8r+8=0 | | (8w)(4w^8z)(0)= | | 2x-3=12x-7 | | (-6+5i)-(7-5i)= | | 6.15+4=37.8225+2x | | 3y^3/4b^3y*10b^2/y | | 0=b^2-8b+115 | | h/9=64/72 |

Equations solver categories